Desenvolvimento de sistemas composicionais a partir da intertextualidade - Lima, Flávio Fernandes de (2011)
This work deals with the creation of Compositional Systems using the Theory of Intertextuality. It shows the hierarchic possibilities between systems, plannings, and works. Three systems were created, and from them, five plannings directed the creation of musical works of three compositions for diverse instrumental formations. These systems and their respective plannings focus on the manipulation of various intertexts, resulting in many degree of abstraction: from literal quotations of musical lines, up to a total disintegration of these intertexts, with complete abscence of their original characteristics. The procedures of intertextual manipulation were based upon the works of Harold Bloom and Joseph Straus, who defined revisionary ratios, which were interpreted and utilized on this dissertation.